The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1186/s43055-021-00471-8
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of central nervous system complications of post-hematopoietic stem cell transplant in pediatric oncology patients: a single institute experience

Abstract: Background Hematopoietic stem cell transplant (HSCT) has been increasingly used in the last few decades, with improved success in offering a cure. CNS complications are an important contributor to morbidity and mortality in HSCT patients. The aim of the study was to evaluate the role of imaging in the detection and assessment of CNSC (central nervous system complications) after HSCT in pediatric oncology patients. The study included consecutive pediatric patients who underwent H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 20 publications
(35 reference statements)
0
2
0
Order By: Relevance
“…The rate is higher in patients with AlloHSCT than in patients with AutoHSCT and reaches up to 70% in some studies [ 7 , 8 ]. In a recently conducted study by Hussein et al, which retrospectively evaluated 525 HSCT recipients, the prevalence was reported to be 13% [ 9 ]. In our study, the prevalence was 7.66% (23/300), which is similar to the rate of 8.67% (26/300) reported by Suxiang Liu et al [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The rate is higher in patients with AlloHSCT than in patients with AutoHSCT and reaches up to 70% in some studies [ 7 , 8 ]. In a recently conducted study by Hussein et al, which retrospectively evaluated 525 HSCT recipients, the prevalence was reported to be 13% [ 9 ]. In our study, the prevalence was 7.66% (23/300), which is similar to the rate of 8.67% (26/300) reported by Suxiang Liu et al [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the study of Hussein et al, the incidence of PRES in post-HSCT recipients was 3.2%, with the most frequent sites being the occipital and parietal regions in 88.2 and 82.4% of the patients, respectively. In their study, diffusion restriction was observed in 29.4% of the cases ( n = 5), and no significant dark signal on ADC maps associated with pseudonormalization was noted in any of the 5 cases [ 9 ]. In our study, restricted diffusion was demonstrated in 2 of 14 PRES patients, one of whom showed isolated cerebellar vermiş involvement.…”
Section: Discussionmentioning
confidence: 99%